The Study Of Competency Model In A Labour Intensive Organization: A Case Study In Alam Flora Sdn Bhd - Hj Ismail, Ekmal Hisham (2006)
It is the fact that employees and HR professionals agreed on the top reasons employees left their organizations are better compensation elsewhere, career opportunity elsewhere and dissatisfaction with potential for career development at organization. About one quarter of employees stated that being ready for a new experience was an important reason to begin or increase the intensity of their job search.